The metabolic and anti-adiposity effects of oral Copaiba-oil supplementation are influenced by sex and obesity - Guareschi, Zoé Maria Neves de Carvalho; Urrutia, Marianela Diaz; Daudt, Beatriz Machado; Siqueira, Bruna S.; Ceglarek, Vanessa Marieli; Dos Santos, Marcia Eduarda; Grassiolli, Sabrina (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2025)
Copaiba oil (CO-oil) is commonly used as a topical healing and anti-inflammatory product in Brazil. However, recent data indicate that oral ingestion of CO-oil has anti-adiposity effects. In the present study, we evaluated the effects of oral CO-oil supplementation on body weight (BW), food intake (FI), adiposity and metabolism in male and female obese and non-obese rats. Monosodium glutamate (MSG; 4g/Kg) was administered during the first week after birth to induce hypothalamic obesity; control (CON; non-obese) rats received equimolar saline. After weaning (30 days of life), MSG and CON males and females were randomly subdivided into CO-oil supplemented (0.5mL/Kg; 3 times/week/8 weeks) and non-supplemented (NS) groups (n = 10-15 rats/group). BW, FI, feed efficiency (FE) and adiposity were registered, as well as fasting glucose (GLU), triglycerides (TGL) and total cholesterol (TC) values. Insulin resistance (IR) was assessed using the triglyceride-glucose index (TyG). Integrative principal component analysis (PCA) showed that chronic CO-oil supplementation alters FI and FE in MSG-obese and non-obese male rats, without modifying adiposity or metabolism. However, CO-oil supplementation of MSG-obese females reduced adiposity, TGL and improved IR, in relation to non-obese females. Thus, our data indicate that CO-oil oral supplementation influences males and females differently, having greater anti-adiposity effects and benefits on the metabolic state of obese female rats.